Spectrum of febrile thrombocytopenia among children in a tropical country-a hospital based observational study in South India - T., Karthikraj; J., Jenish Rajma; R. V., Jeyabalaji; Kuttuva, Shivani (International Journal of Contemporary Pediatrics, 2021)
Background: Febrile thrombocytopenia is a common reason for pediatric admission. Though infections are the major cause, noninfectious causes are not uncommon. This study was done to estimate the prevalence of thrombocytopenia as a presentation in pediatric fever cases, to analyze the various etiologies, presentations and relationship between platelet count and the severity of disease and prognosis. Methods: Retrospective observational study done by collecting data from hospital records of children admitted in Velammal Medical college hospital from January 2016 to December 2017. Children in the age group of 6 months to 15 years with fever and thrombocytopenia at admission were included in the study. Children on treatment with anti-platelet drugs, other chronic diseases and infants less than 6 months were excluded. Results: Out of 2523 fever cases admitted, 372 children fulfilled this criterion. 70% had positive dengue serology, other infectious causes were other viral hemorrhagic fevers, complicated enteric fever, scrub typhus and sepsis. The predominant non-infectious causes were hematological malignancies, Idiopathic thrombocytopenic purpura and Hemolytic uremia syndrome. Conclusions: Febrile thrombocytopenia is a common clinical presentation in children in dengue endemic areas. Most viral fevers have leukopenia but presence of thrombocytopenia with warning signs like pain abdomen, vomiting or oliguria should prompt suspicion of dengue. Infections like enteric fever, scrub typhus or chikungunya may also mimic similar findings. Rarely diseases like leukemia, Idiopathic thrombocytopenic purpura, Hemolytic uremic syndrome or Sepsis may also present as febrile thrombocytopenia. The need for antibiotics or blood products is very minimal.